![22 \div 2 \sqrt{3 } - 1 + 17 \div 2 \sqrt{3} - 1 \\ \\ \\ \\ \\ \\ 22 \div 2 \sqrt{3 } - 1 + 17 \div 2 \sqrt{3} - 1 \\ \\ \\ \\ \\ \\](https://tex.z-dn.net/?f=22+%5Cdiv+2+%5Csqrt%7B3++%7D++-+1+%2B+17+%5Cdiv+2+%5Csqrt%7B3%7D++-+1+%5C%5C++%5C%5C++%5C%5C++%5C%5C++%5C%5C++%5C%5C+)
Answers
Answered by
0
Answer:
I hope kddjuwegs. djhw
Answered by
0
22 ÷ 2
1 + 17 ÷ 2
- 1=![\dfrac{(13\sqrt{3} -4)}{2} \dfrac{(13\sqrt{3} -4)}{2}](https://tex.z-dn.net/?f=%5Cdfrac%7B%2813%5Csqrt%7B3%7D+-4%29%7D%7B2%7D)
Step-by-step explanation:
We have,
22 ÷ 2 - 1 + 17 ÷ 2
- 1
To find, the value of 22 ÷ 2 - 1 + 17 ÷ 2
- 1=?
∴ 22 ÷ 2 - 1 + 17 ÷ 2
- 1
∴ 22 ÷ 2- 1 + 17 ÷ 2
- 1=
Hence, 22 ÷ 2 1 + 17 ÷ 2
- 1=
Similar questions